2020
DOI: 10.1093/geronb/gbaa181
|View full text |Cite|
|
Sign up to set email alerts
|

Ageism Linked to Culture, Not Demographics: Evidence From an 8-Billion-Word Corpus Across 20 Countries

Abstract: Objectives Ageism has increased over 200 years and costs the US healthcare system $63 billion a year. While scholars agree on the consequences of ageism, there are disagreements on whether it is related to the demographics of aging, or society’s cultural values. We test both hypotheses across 20 countries. Methods To circumvent the sampling limitations of survey studies, we used an 8-billion-word corpus, identified three syno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 35 publications
1
57
0
1
Order By: Relevance
“…Ageism was also associated with dementia-related anxiety or the fear of developing Alzheimer's disease and related dementias [28]. Nevertheless, at the structural level, ageism has been shown to be linked to cultural aspects such as greater levels of masculinity and long-term orientation ("the extent to which a culture programs its members to accept delayed gratification of their material, social, and emotional needs") [29]. Ageism has shown to be significantly reduced when the percentage of older adults is greater and with greater increases in life expectancy [30].…”
Section: Ageism and Adverse Outcomesmentioning
confidence: 99%
“…Ageism was also associated with dementia-related anxiety or the fear of developing Alzheimer's disease and related dementias [28]. Nevertheless, at the structural level, ageism has been shown to be linked to cultural aspects such as greater levels of masculinity and long-term orientation ("the extent to which a culture programs its members to accept delayed gratification of their material, social, and emotional needs") [29]. Ageism has shown to be significantly reduced when the percentage of older adults is greater and with greater increases in life expectancy [30].…”
Section: Ageism and Adverse Outcomesmentioning
confidence: 99%
“…In general, Eastern Asian cultures are known to have a higher respect for older adults than Western culture [ 25 ]. Ageism is a concept interpreted within the social and cultural context [ 35 ]; this result should take the Korean socio-cultural environment into account, specifically the rapid increase in the older adults population [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Donizzetti [ 45 ] reported a positive correlation between age and ageism, while Kim and Ha [ 16 ] found that age is not associated with ageism. Cultural factors that are rapidly increasing the aging population in South Korea could also affect ageism [ 35 ]. Since our study was conducted with nursing students between the ages of 18 and 29, the age range is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies [38][39][40][41][42][43] controlled for GDP per capita to test the possible influence of level of development or modernization on ageism. In keeping with these studies, we controlled for GDP per capital to test the influence of a country's level of development on societal perceptions of caregivers.…”
Section: Covariate: Gdp Per Capitamentioning
confidence: 99%